Kearifan Lokal sebagai Media Pembelajaran Bahasa Asing - Lestuny, Carolina; Tomasouw, Jolanda; Akihary, Wilma; Soumokil, Piet (Universitas Pattimura, 2024)
Media plays important role in creating enjoyable learning. It produces active, creative and interactive student attitudes. Learning German using local wisdom as a learning media aims to (1) utilize cultural richness in learning German (2) as motivation in maintaining local wisdom in one's own region (3) increase student participation in the process of learning foreign languages, especially German in the classroom. This activity involves teachers and students of SMAN 3 Tual, Southeast Maluku. The data to be obtained through instruments in the form of questionnaires and interviews. The methods used are interactive lectures and discussions. The results of the activities obtained are that students and teachers have the motivation to utilize local wisdom in their own region and open up ideas for teachers in developing German language learning in the classroom by utilizing the available local wisdom.